A STUDY OF VMI-BASED PROCUREMENT SYSTEM IMPLEMENTATION AT INDONESIAN AEROSPACE FOR PERISHABLE MATERIAL - NANDA PUTRA NIM : 94515001 , REDO
Indonesian Aerospace (IAe) has a problem on how to determine optimal replenishment lot size for their perishable material which have stochastic demands. Such material will perish when it is exposed to any certain extreme condition (e.g.: temperature, humidity). If IAe store so much perishable materials then material services can be maximized in expense of high holding and deterioration cost; otherwise component’s production schedule may disrupted by material shortages which incurs high penalty for IAe. Moreover, the condition just got worse with subpar condition of the materials itself when it arrives because of very long procurement lead time. Thus IAe is in dire need to implement new system which capable of handling such conditions. In order to solve the problem, it is advised to switch the procurement system to Vendor Managed Inventory (VMI), which is an alliance-based procurement system. VMI is a procurement system where the vendor takes charge of material replenishment and inventory management, in exchange for buyer’s long term commitment and access to buyer’s material requirement plan and stock level. This system is advised because of its responsiveness, where the material will be replenished immediately when any triggers happened (e.g. stock level fall below minimal threshold, replenishment period has already passed). Unfortunately, its implementation process is complicated. Without an integrated concept and meticulous planning, VMI might results in anything less than satisfactory. Thus this study is conducted to facilitate such requirement from two perspectives: academic and practice, so that a comprehensive view of the subject can be obtained. Academically, VMI is an optimization of inventory policies that applies to across eselons; whilst practically VMI is shift from transactional-based interaction to perpetual interaction with dedicated vendor(s). Both perspectives are summarized into five stages of an implementation plan: 1. Business Process Evaluation; 2. Inventory Policies Targeting; 3. VMI Planning; 4. Critical Clausal in Contract; 5. Information System Integration. This plan is specifically designed for IAe case study or any manufacturer alike. This paper models VMI with specific characteristics such as: 1) perishable materials; 2) stochastic demand; 3) No value-addition process to the material across two eselons. The model is then simulated using iterative procedure and expects that: vendor may gain additional 55% on stable income from IAe; whilst IAe can reduce its expenditure by 48%, along with improved inventory turnover to 137. Time required for this implementation is 32 weeks which involves both buyer’s and vendor’s representatives. Last but not least, this paper also offers two methods of integrating vendor and buyer’s information system: either by self-develop Network Portal or outsource it to third party owned Value Added Network.